IntelliCage Automated Behavioral Phenotyping Reveals Behavior Deficits in the 3xTg-AD Mouse Model of Alzheimer’s Disease Associated With Brain Weight - Winslow, Wendy; McDonough, Ian; Tallino, Savannah; Decker, Annika; Vural, Austin S.; Velazquez, Ramon (Frontiers in Aging Neuroscience, 2021)
Transgenic rodent models of Alzheimer’s Disease (AD) were designed to study mechanisms of pathogenesis and connect these mechanisms with cognitive decline. Measurements of cognition in rodents can be confounded, however, by human handling and interaction; the IntelliCage was created to circumvent these issues while measuring various facets of cognition in a social environment with water consumption as the primary motivator for task completion. Here, for the first time, we examined behavioral performance of 3xTg-AD mice in the IntelliCage. Seven- to nine-month-old female 3xTg-AD and non-transgenic mice were tested for 29 days in the IntelliCage to measure prefrontal cortical and hippocampal function. We found that a higher percentage of NonTg mice were able to successfully complete the training (adaptation) phases compared to their 3xTg-AD counterparts. Furthermore, the 3xTg-AD mice showed impairments in attention and working memory. Interestingly, we found that differences in body and brain weight between NonTg and 3xTg-AD mice were associated with whether mice were able to complete the IntelliCage tasks. Mechanistically, 3xTg-AD mice that completed IntelliCage tasks had lower cortical insoluble amyloid-β40 fractions than their 3xTg-AD counterparts who failed to complete the tasks. Collectively, these results demonstrate deficits in cognition in the 3xTg-AD mouse and inform scientists of important factors to consider when testing this transgenic model in the IntelliCage.